Variety in written English : texts in society : societies in text - Bex, Tony, 1943- (Interface (London, England), 1996)
Combining insight from a variety of linguistic perspectives including Hallidayan functional linguistics and relevance theory, Tony Bex demonstrates how written texts operate within society to convey meaning.